Remaking the voyage : new essays on Malcolm Lowry and In ballast to the White Sea - Tookey, Helen, 1969-; Biggs, Bryan (Liverpool English texts and studies, 2020)
An Open Access edition of this book is available on the Liverpool University Press website and the OAPEN library. 'Who ever thought they would one day be able to read Malcolm Lowry's fabled novel of the 1930s and 40s, In Ballast to the White Sea? Lord knows, I didn't' - Michael Hofmann, TLS This book breaks new ground in studies of the British novelist Malcolm Lowry (1909-57), as the first collection of new essays produced in response to the publication in 2014 of a scholarly edition of Lowry's 'lost' novel, In Ballast to the White Sea. In their introduction, editors Helen Tookey and Bryan Biggs show how the publication of In Ballast sheds new light on Lowry as both a highly political writer and one deeply influenced by his native Merseyside, as his protagonist Sigbjørn Hansen-Tarnmoor walks the streets of Liverpool, wrestling with his own conscience and with pressing questions of class, identity and social reform. In the chapters that follow, renowned Lowry scholars and newer voice...